Specification mining for digital circuits - Lim, Zhi Xian (2016)
During the verification of a hardware system, one of the most important steps is formal specification which is used to describe a system and to analyze its behaviors. However, manually creating a complete set of formal properties is difficult and time-consuming process. Thus, specification mining approach for digital circuit has been proposed to automatically generate the formal specification. The specification mining tool will be developed to help for better understanding digital circuits. Firstly, this specification mining tool will take a set of simulation traces and several event definitions as input. Secondly, specification mining algorithm will be designed to mine out the predefined template from traces. This is a software project where no hardware implementation is required.